2016
DOI: 10.1111/acps.12558
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal association between cognitive performance and obsessive–compulsive symptoms in patients with psychosis and unaffected siblings

Abstract: Although insight into causality needs further exploration, our results do not confirm the hypothesis of pre-existing cognitive risk constellations. Findings suggest that remission of comorbid OCS results in improved immediate verbal recall and processing speed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
3
7
0
Order By: Relevance
“…The longitudinal results partly stand in line with results of previous analyses from the GROUP data, comparing OCS status groups and the course of PANSS and GAF scores [ 38 ] as well as cognitive functioning over the 3 year assessment period [ 37 ]. In all three studies at baseline, the group which was going to develop OCS at follow-up—the OCS de novo group—already showed more impairment than the no-OCS group.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The longitudinal results partly stand in line with results of previous analyses from the GROUP data, comparing OCS status groups and the course of PANSS and GAF scores [ 38 ] as well as cognitive functioning over the 3 year assessment period [ 37 ]. In all three studies at baseline, the group which was going to develop OCS at follow-up—the OCS de novo group—already showed more impairment than the no-OCS group.…”
Section: Discussionsupporting
confidence: 85%
“…To study the course of OCS and its relationship with the course of motor symptoms both OCS and motor symptoms were categorized into four groups as was done in our previous analyses [ 37 , 38 ]: (1) a no symptom group, (2) a remission group, showing symptoms at baseline assessment only, (3) a de novo group, showing symptoms at follow-up, but not at baseline and (4) a persistent group, showing symptoms at both assessments. Subsequently, the relationship between those groups and motor symptoms was analyzed (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is still debated whether cognitive impairment associated to comorbid OCS in schizophrenia precedes the onset of OCS (Poyurovsky et al, 2012) or, alternatively, it represents their consequence (Moritz et al, 2012;Schirmbeck et al, 2016). Our finding of a dependency of PS on OCS severity would support the view that additional cognitive deficits related to OCS comorbidity may have a "state" component.…”
Section: Discussionsupporting
confidence: 66%
“…In cases, where authors provided us with full data sets of correlational or unpublished data, we used a YBOCS score of 8 as the cut-off to define the comorbid (OCS +) group, since this was a commonly used cut-off value in the references we included [32][33][34][35][36]. Analyses were restricted to the per study level,for instance, reported subgroups based on disease duration were combined into one OCS + and one OCS− group [37].…”
Section: Data Synthesis and Statistical Analysismentioning
confidence: 99%